Information Literacy of Tuberculosis Patients in Hospital Health Services - Silvana, Hana; Heryadi, Hedi (Edulib, 2024)
In implementing health service management, the role of communication is needed, because it must determine the cause of a disease in a patient. Therefore, knowledge and communication skills must be possessed by all health workers, because they will influence patient perceptions, patient assessments of services, trust, and patient recovery rates. The research method used is a qualitative approach, data collection techniques through interview methods aim to obtain information from participants or sources through direct face-to-face dialogue between researchers and sources. The concept of information literacy standards is composed of three basic components, namely access, evaluation, and use. Patients in the millennial category browse the internet to find out more about this disease. On the internet site, the explanation is clearer and more detailed. Apart from that, health service information is also obtained in the form of banners, posters, pamphlets, or other printed media available at the health service facility. The research conducted showed that tuberculosis patients could develop information literacy about the need for information about the disease they were suffering from. This ability accesses, evaluates, and utilizes the required information. Fulfilling information needs related to their illness is available through information services available at the health center where their health facility is located or at the referral hospital where they seek treatment.